The role of dental pain and psychosocial factors on the relationship between dental caries and oral health-related quality of life in children - Cilio Antonio Ribeiro Junior; Mario Vianna Vettore; Janete Maria Rebelo Vieira; Ana Paula Corrêa de Queiroz Herkrath; Adriana Corrêa de Queiroz Herkrath; Juliana Vianna Pereira; Fernando José Herkrath; Maria Augusta Bessa Rebelo (BMC, 2022)
Abstract Background To examine the role of dental pain, sense of coherence (SOC) and social support on the relationship between dental caries and oral health-related quality of life (OHRQoL) in children aged 12 years. Methods A cross-sectional study involving 400 schoolchildren selected from public schools in a socioeconomically disadvantaged region in the city of Manaus, Brazil was carried out. The predictors of OHRQoL were selected according to the Wilson and Cleary theoretical model, including number of decayed teeth and its clinical consequence (component D of the DMFT index and PUFA/pufa index), dental pain (symptom status), and SOC and social support (individual and environmental characteristics). Statistical analysis was conducted through structural equation modelling and multivariable negative binomial regression. The significance level established for all analyses was 5%. Results Number of dental caries was indirectly linked with OHRQoL (β = 0.19, 95% CI 0.11/0.29) through dental pain, SOC and social support. Clinical consequences of untreated caries directly predicted poor OHRQoL (β = 0.12, 95% CI 0.01/0.23). Dental pain, SOC and social support did not moderate the effect of dental caries measures on OHRQoL. Conclusion Our findings suggest the role of dental pain, SOC and social support as mediator factors on the link between dental caries and OHRQoL. Tackling dental caries along with psychosocial factors may attenuated the impact of oral health on OHRQoL in children.